ANALISIS HASIL PENGUKURAN KUALITAS DAYA ENERGI LISTRIK PADA INDUSTRI TEKSTIL - Hasan, Achmad (Badan Pengkajian dan Penerapan Teknologi, 2012)
Primary energy used in the production process of PT. Textile Industries is the electric energy and thermal energy. The electrical energy supplied by PT. PLN (Persero) with contractual power of 5540 kVA, and has 5 units with a capacity of 2500 kVA transformer (1 unit), 2,000 kVA (2 units), and 1,250 kVA (2 units). From the analysis of several potential energy saving electrical system supply side can be recorded as follows: An unbalanced load can result in decreased system efficiency by 2%. Optimizing the performance of the capacitor bank regulators so that the work factor to achieve an optimum value (0.9). Losses incurred due to the low power factor can be calculated based on the following approaches: Losses = [1 -pflow/pfhigh2] x 100%. Losses in the transformer-1 (2000 kVA) is 479.8 kW, transformer-3 (2000 kVA) is 834.2 kW, transformer-4 (1250 kVA) is 521.4 kW, and transformer-5 (1250 kVA) is 125 kW. Current THD (total harmonic distortion) reduction to < 5%. Replacement tranformator so in accordance with the optimum loading and maximum efficiency from 9000 kVA to 6660 kVA. This replacement will reduce losses as high as zero load is usually equal to 3%.